Parametric analysis of energy harvesting pavements operated by air convection - Chiarelli, Andrea; Dawson, Andrew; Garcia, Alvaro (Elsevier, 2015)
In this paper, an energy harvesting pavement prototype using air as the operating fluid is described and analysed. The prototype harvests the thermal energy available in the pavement through pipes embedded in its structure, where air flows thanks to natural convection. The air is able to exit the system through an updraft chimney. A parametric analysis of the controllable parameters of interest is performed in this work in order to evaluate the variation in the performance of the energy harvesting prototype in different experimental setups. This study shows that there exists a maximum value for the air speed in each configuration and that the energy harvesting efficiency depends on the height and the diameter of the chimney. Moreover, there is a minimum value of the chimney diameter that does not allow air movement and makes the whole system behave as if no pipes were embedded in the pavement structure.